Extreme inflation and time-varying expected consumption growth - Ilya Dergunov; Christoph Meinerding; Christian Schlag (Leibniz Institute for Financial Research SAFE, 2022)
In a parsimonious regime switching model, we find strong evidence that expected consumption growth varies over time. Adding inflation as a second variable, we uncover two states in which expected consumption growth is low, one with high and one with negative expected inflation. Embedded in a general equilibrium asset pricing model with learning, these dynamics replicate the observed time variation in stock return volatilities and stockbond return correlations. They also provide an alternative derivation for a measure of time-varying disaster risk suggested by Wachter (2013), implying that both the disaster and the long-run risk paradigm can be extended towards explaining movements in the stock-bond correlation.
urn:nbn:de:hebis:30:3-619992
Keywords: E31; E44; G12; 330; Long-run risk; inflation; recursive utility; filtering; disaster risk